Local distance antimagic chromatic number for the union of star and double star graphs - Priyadharshini, V.; Nalliah, M. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 519.17Let $G=(V,E)$ be a graph on $p$ vertices with no isolated vertices. A bijection $f$ from $V$ to $ \{1,2,3,… ,p\}$ is called a local distance antimagic labeling if, for any two adjacent vertices $u$ and $v,$ we receive distinct weights (colors), where a vertex $x$ has the weight $w(x)=\displaystyle\sum olimits_{vε N(x)} f(v).$ The local distance antimagic chromatic number $χ_{lda}(G)$ is defined as the least number of colors used in any local distance antimagic labeling of $G.$ We determine the local distance antimagic chromatic number for the disjoint union of $t$ copies of stars and double stars.